Poison dart frogs [book with audioplayer] - Koestler-Grack, Rachel A., 1973- (Blastoff! readers. Animals of the rain forest., 2019)
The brilliantly colored poison dart frog communicates with its skin. Its bright colors signal predators that this frog is poisonous. Read about this amazing creature's other physical features and behavior in this book that explores where a poison dart frog lives, what food it eats, and how and where it sleeps.